Collective empowerment of women from the social solidarity economy at the Centéotl Community Development Center, Oaxaca, Mexico - Jiménez López, Raquel; Torres Carral, Guillermo Arturo (Cooperativismo & Desarrollo, 2023)
The outstanding feature of the word empowerment is power, which can be analyzed from a multidimensional or dualistic perspective. Among the most relevant dualisms, two conceptualizations are distinguished: 1) Collective power includes three forms: power with, power for, and power from within, these are positive because when one subject acquires them, others also obtain them; and 2) Individual power or power over is negative, because the one who obtains it places himself above others. In the context of the Social Solidarity Economy, (ESS) collective power is developed because its principles foster reciprocal relationships. From this perspective, the article exposes the results of a qualitative research of an SSE organization: Center for Community Development Centéotl A. C. located in Oaxaca, Mexico with the objective of identifying if the association’s programs promote the collective empowerment of women. It has been verified in two Centéotl programs; Bancomunidad and Escuela Campesina the existence of a collective empowerment, result of promoting economic activities through technical training or financing and educational training in SSE through active and collective participation.